Perceptions of Adherence The Use of Type 2 Anti-Diabetic Drug: Preliminary Study With Health Belief Theory Model - Maria Nathalia Intan Istianti; Aris Widayati (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
Diabetes Mellitus (DM) is a disease characterized by blood sugar levels above the standard value. One of the DM therapy’s managemen is pharmacological therapy. The use of medicines that comply with the instructions of use is one of the determinant factors for therapy success in type 2 DM patients. This study aims to explore the perceptions of DM patients regarding their medication adherence. This research is a qualitative approachby interviewing respondents. The perceptions of medication adherence were explored among the 20’s outpatient type 2 DM patients at Bali Royal Hospital, Denpasar, Bali. The six constructs of the Health Belief Model theory were applied. Data were analyzed with a content analysis approach. The results found that regarding Perceived Susceptibility and Perceived Severity constructs, the respondents believed they would be susceptible to hyperglycemia, and their disease will worsen if they are not devoted to using antidiabetic medicines. Perceived Benefit construct shows that respondents believed in medication adherence in maintaining their health. Respondents' Perceived Barrier revealed that their laziness and disregarded in taking their medications are the obstacles. Their strong will to get healthy represents the Cues of Action construct that would trigger their medication adherence. Finally, the selfEfficacy construct exposed respondents' confidence regarding medication adherence. Respondents' beliefs on Perceived Susceptibility, Severity, Benefit, Cues of Actions and Self-Efficacy help respondents to adhere using antidiabetic medicines. Perceived Barrier which respondents believe provides an obstacle to adhering using antidiabetic medicines.